Exploring the Impact of Multilingualism on Learning Outcomes in Ethnically Diverse Educational Settings - Auong, Thuira; Sein, Min Aung; Kyi, Thida Suu (Educia Journal, 2023)
The purpose of this paper is to investigate the effects of multilingualism on learning achievements across various education types in Myanmar. Qualitative research methodology was used in the study and involved conducting semi structured interviews, focus group discussions and classroom observations to capture the experiences, the challenges and perception of students, teachers, parents and educational administrators. In all, 50 purposively selected participants from multilingual communities responded to questions about the enablers and barriers to education arising from linguistic diversity. Consequently, it is noted that however, multilingualism benefits students through increased participation, cultural sense, and improved learning abilities, the major problems arising are language accord, qualified teachers, and limited teaching materials. Despite the best efforts from the teachers to apply meaningful translanguaging approaches for learning, they encounter several problems while doing so without organization backing. Thus, while students and teachers preferred instruction in first languages, parents and administrators had conflicts of interest between local language education and instruction n national languages. This research also fills the research gaps by presenting paradigmatic data from a developing country with high multilingual population. There is, therefore, a call for inclusive and adequate and sufficient policies, resources and training of teachers in order to maximize on the gains of multilingual education as well as to overcome setbacks. The study extends the global understanding of multilingual education as a development policy by shedding light on the challenges of implementing the policy in low resource districts.